Designing mobile health to align with the social determinants of health - Rogers, Courtney C.; Jang, Sophia S.; Tidwell, Whitney; Shaughnessy, Sarah; Milburn, Juliane; Hauck, Fern R.; Williams, Ishan C.; Valdez, Rupa S. (Frontiers in Digital Health, 2023)
The maternal health crisis in the United States is becoming increasingly worse, with disparities continuing to escalate among marginalized populations. mHealth can contribute to addressing the Social Determinants of Health (SDOH) that produce inequities in maternal morbidity and mortality. Reducing inequities through mHealth can be achieved by designing these technologies to align with SDOH. As mHealth developed to support maternal health has primarily supported the extension of clinical care, there is an opportunity to integrate frameworks and methods from human factors/ergonomics and public health to produce thorough comprehension of SDOH through intentional partnerships with marginalized populations. Potential for this opportunity is presented through a case study derived from a community-based participatory research process focused on transportation access to maternal health services. Through multi-faceted, interdisciplinary, and community-based approaches to designing mHealth that attends to the systemic factors that generate and escalate inequities, improvements in the maternal health crisis could be realized.